2021
DOI: 10.1002/1873-3468.14137
|View full text |Cite
|
Sign up to set email alerts
|

Asp56 in actin is critical for the full activity of the amino acid starvation‐responsive kinase Gcn2

Abstract: Eukaryotes harbour a conserved signalling pathway, called General Amino Acid Control (GAAC) in Saccharomyces cerevisiae, for overcoming amino acid starvation. Upon starvation, the protein kinase Gcn2, which phosphorylates the eukaryotic translation initiation factor eIF2α, becomes stimulated to trigger the GAAC response. Genetic studies suggest that Yih1, which is the yeast homolog of mammalian IMPACT and which binds monomeric actin, inhibits Gcn2 when released from actin. Here, we found that D56A substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The cue that triggers Yih1/IMPACT to inhibit Gcn2 remains to be uncovered. So far it is only known that actin dynamics affects IMPACT's ability to inhibit Gcn2 [ 25 , 29 ]. Gir2 in yeast, or DFRP2 in mammals, also contains an N-terminal RWD domain, and so far for Gir2 it has been shown that it inhibits Gcn2 by binding to Gcn1, as found for Yih1/IMPACT [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cue that triggers Yih1/IMPACT to inhibit Gcn2 remains to be uncovered. So far it is only known that actin dynamics affects IMPACT's ability to inhibit Gcn2 [ 25 , 29 ]. Gir2 in yeast, or DFRP2 in mammals, also contains an N-terminal RWD domain, and so far for Gir2 it has been shown that it inhibits Gcn2 by binding to Gcn1, as found for Yih1/IMPACT [ 30 ].…”
Section: Introductionmentioning
confidence: 99%